2014
DOI: 10.1093/infdis/jiu565
|View full text |Cite
|
Sign up to set email alerts
|

Diversity-Oriented Synthesis Probe TargetsPlasmodium falciparumCytochrome b Ubiquinone Reduction Site and Synergizes With Oxidation Site Inhibitors

Abstract: Background. The emergence and spread of drug resistance to current antimalarial therapies remains a pressing concern, escalating the need for compounds that demonstrate novel modes of action. Diversity-Oriented Synthesis (DOS) libraries bridge the gap between conventional small molecule and natural product libraries, allowing the interrogation of more diverse chemical space in efforts to identify probes of novel parasite pathways.Methods. We screened and optimized a probe from a DOS library using whole-cell ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 28 publications
1
38
0
Order By: Relevance
“…To determine the compound’s mechanism of action, MLP generated ML238-resistant parasites and conducted whole-genome sequencing. These studies revealed that ML238 acts at the quinone reductase site of the bc 1 complex (Q 1 ) (Lukens et al , 2014), which is on the opposite side of the cell membrane from the quinol oxidase site targeted by the antimalarial drug atovaquone. ML238 and atovaquone lacked cross-resistance and were synergistic in combination, highlighting the quinone reductase site as a antimalarial therapeutic target that may overcome atovaquone resistance (Lukens et al , 2014).…”
Section: Bridging the Chasmmentioning
confidence: 99%
“…To determine the compound’s mechanism of action, MLP generated ML238-resistant parasites and conducted whole-genome sequencing. These studies revealed that ML238 acts at the quinone reductase site of the bc 1 complex (Q 1 ) (Lukens et al , 2014), which is on the opposite side of the cell membrane from the quinol oxidase site targeted by the antimalarial drug atovaquone. ML238 and atovaquone lacked cross-resistance and were synergistic in combination, highlighting the quinone reductase site as a antimalarial therapeutic target that may overcome atovaquone resistance (Lukens et al , 2014).…”
Section: Bridging the Chasmmentioning
confidence: 99%
“…Inhibition at either site is sufficient to block the catalytic cycle of cyt bc 1 (Q cycle), which ultimately leads to pyrimidine starvation and cell death in P. falciparum (4,5). To date, pyridones (6,7), naphthoquinones (8,9), acridones (10), quinolones (11)(12)(13), and benzene sulfonamides (14) have been identified as potent inhibitors of Plasmodium cyt bc 1 (15). This includes atovaquone (ATV), which targets the Q o site of the P. falciparum cytochrome bc 1 complex (16).…”
mentioning
confidence: 99%
“…Aside of atovaquone, other bc1 complex inhibitors were described, as acridones [78], quinolones [79][80][81], pyridones [82,83], and benzene sulfonamides [84]. Although many compounds have presented inhibitory potential against bc1 complex, this target might be considered underexploited, since the majority of these compounds target the Qo site [85].…”
Section: Cytochrome Bc1 (Complex Iii)mentioning
confidence: 99%